DIDACTIC PRINCIPLES OF USING INFORMATION AND COMMUNICATION TECHNOLOGIES IN AN ELECTRONIC INFORMATION EDUCATION ENVIRONMENT - Asallayev O’ktam Khayriddinovich (Journals Park Publishing, 2024)
This article is devoted to the didactic principles of using information and communication technologies in the e-learning environment and the issues of organizing educational activities based on these principles. feedback on their widespread implementation and effective use is provided.
Keywords: Educational system, electronic information educational environment, teaching process, electronic educational resources, modern technologies, didactic principles, educational material, pedagogical activity.